Self-organized nanocomb of ZnO fabricated by Au-catalyzed vapor-phase transport - Yu, M. B. (2012)
Based on a vapor-phase transport process, self-organized nanocomb structures of ZnO were fabricated on Au-coated Si substrate by employing a mixture of ZnO and graphite powders as source materials. The morphology of the product showed a ribbon-like stem and nanorod array aligned evenly along one side of the nanoribbon. It was found that the nanoribbon grew mainly along [1 0 1 ̅ 0] direction and the self-assembled branching nanorods grew epitaxially along [0 0 0 1] orientation from the (0 0 0 2) plane of the stem. The growth process was analyzed in detail.